(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The problem of defining the essence of usufruct is covered. The current aspect of this problem from the point of view of the Concept of developing the civil legislation is analyzed. Dominant features of this right are viewed, some trends of perfecting usufruct are defined.